2012
DOI: 10.1371/journal.pgen.1003058
|View full text |Cite|
|
Sign up to set email alerts
|

RHOA Is a Modulator of the Cholesterol-Lowering Effects of Statin

Abstract: Although statin drugs are generally efficacious for lowering plasma LDL-cholesterol levels, there is considerable variability in response. To identify candidate genes that may contribute to this variation, we used an unbiased genome-wide filter approach that was applied to 10,149 genes expressed in immortalized lymphoblastoid cell lines (LCLs) derived from 480 participants of the Cholesterol and Pharmacogenomics (CAP) clinical trial of simvastatin. The criteria for identification of candidates included genes w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 33 publications
(28 citation statements)
references
References 34 publications
(42 reference statements)
0
27
0
Order By: Relevance
“…Recently, we have successfully used a similar approach to identify RHOA as a novel determinant of LDL-cholesterol response to statin treatment 9 . Although cellular phenotyping of LCLs has long been employed to functionalize the molecular impact of genetic variation associated with elevated cholesterol levels 2-4, 6, 9 , to our knowledge this is the first instance of capitalizing on the inter-individual variation of a cellular phenotype within LCLs to identify novel genes involved in cellular cholesterol homeostasis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, we have successfully used a similar approach to identify RHOA as a novel determinant of LDL-cholesterol response to statin treatment 9 . Although cellular phenotyping of LCLs has long been employed to functionalize the molecular impact of genetic variation associated with elevated cholesterol levels 2-4, 6, 9 , to our knowledge this is the first instance of capitalizing on the inter-individual variation of a cellular phenotype within LCLs to identify novel genes involved in cellular cholesterol homeostasis.…”
Section: Discussionmentioning
confidence: 99%
“…For example, given the unclear genetic background of familial combined hyperlipidemia (FCHL), expression array analysis of LCLs from FCHL patients versus healthy controls was used to identify disease-specific transcriptomic profiles 8 . Through expression array analysis of 480 in vitro simvastatin and sham incubated LCLs derived from participants of the Cholesterol and Pharmacogenetics (CAP) statin clinical trial, we recently reported the identification of RHOA as a novel candidate gene implicated in LDL-cholesterol lowering in response to statin treatment 9 . Since HMGCR encodes the rate-limiting enzyme of the cholesterol biosynthesis pathway and is tightly regulated at the level of gene transcription by sterol response element binding factor 2 (SREBF2) in response to changes in intracellular sterol content 10 , we identified genes whose statin-induced expression level changes were most highly correlated with statin-induced changes in HMGCR .…”
Section: Introductionmentioning
confidence: 99%
“…Whole transcriptome sequencing (RNA-seq) was performed on LCLs from eight African American individuals (seven female and one male) as previously described (48). Libraries were sequenced on an Illumina GAII machine and aligned to hg19 using TopHat v1.2.0 and Bowtie v0.12.7 (49,50).…”
Section: Methodsmentioning
confidence: 99%
“…Novel junctions were validated using RT-PCR with Sanger sequencing. The effect of SUGP1 on the stability of these HMGCR transcripts was assessed in HepG2 and Huh7 cells incubated with actinomycin D, with transcript half-life calculated as previously described (48). …”
Section: Methodsmentioning
confidence: 99%
“…In a systematic manner, this can be achieved by analyzing cells, either by quantifying functional readouts upon candidate gene knockdown and overexpression, as discussed in my own presentation [10], or by comparing functional insights obtained from patient-derived cells with their respective geno types. Following the latter strategy in lympho blasts, Ron Krauss (Children's Hospital, Oakland Research Institute, CA, USA) and Marisa Wang Medina (Children's Hospital, Oakland Research Institute) reported several novel genes for which expression correlates with that of HMGCR and is induced by statins [11], among them GATM, RHOA and HNRNPA1. Interestingly, for RHOA and HNRNPA1, distinct isoforms appear to differentially affect cellular cholesterol levels and the expression of lipid-regulatory genes, which hints at a little-explored layer of lipid metabolism regulation.…”
Section: Approaches To New Pathway Discoverymentioning
confidence: 99%